Contribución de los manglares a las pesquerías de la Bahía de Panamá - D’Croz, Luis; Kwiecinski, Bogdan (Revista de Biología Tropical, 1980)
The expansion of Panama City created the threat of eliminating the Juan Díaz mangrove swamps on the east side of the city. Studies of the fishery and the ecological importance of these swamps show that many commercially important fishes and almost all the species of commercially important shrimp depend on these swamps during the early stages of their life cycles. Estimates of the contribution of the Juan Díaz mangrove swamps to the Panama Bay Fisheries are in the order of a million dollars per year, and their elimination would greatly affect the ecological balance of a large section of the Pacific coast of Panama.